A History of Neonatal Medicine—Past Accomplishments, Lessons Learned, and Future Challenges. Part 1—The First Century - Lussky, Richard C. (Pediatric Pharmacy Advocacy Group, 2005)
This is the first of two articles that will review the history of neonatal medicine. This article will describe the beginnings of the modern era of newborn medicine, review pharmacological misadventures, and describe recent advances in the fields of neonatal and perinatal medicine.